Online Continuing Education for Expanding Clinicians' Roles in Breastfeeding Support. (November 2015) - Edwards, Roger A.; Colchamiro, Rachel; Tolan, Ellen; Browne, Susan; Foley, Mary; Jenkins, Lucia; Mainello, Kristen; Vallu, Rohith; Hanley, Lauren E.; Boisvert, Mary Ellen; Forgit, Julie; Ghiringhelli, Kara; et al.
Lack of health professional support is an important variable affecting mothers' achievement of breastfeeding goals. Online continuing education is a recognized pathway for disseminating content for improving clinicians' knowledge and supporting efforts to change practices. At the time we developed our project, free, accredited continuing education for physicians related to breastfeeding management that could be easily accessed using portable devices (via tablets/smartphones) was not available. Such resources were in demand, especially for facilities pursuing designation through the Baby-Friendly Hospital Initiative. We assembled a government, academic, health care provider, and professional society partnership to create such a tutorial that would address the diverse content needed for supporting breastfeeding mothers postdischarge in the United States. Our 1.5-hour-long continuing medical and nursing education was completed by 1606 clinicians (1172 nurses [73%] and 434 physicians [27%]) within 1 year. More than 90% of nurses and over 98% of physicians said the tutorial achieved its 7 learning objectives related to breastfeeding physiology, broader factors in infant feeding decisions and practices, the American Academy of Pediatrics' policy statement, and breastfeeding management/troubleshooting. Feedback received from the tutorial led to the creation of a second tutorial consisting of another 1.5 hours of continuing medical and nursing education related to breast examination and assessment prior to delivery, provision of anticipatory guidance to pregnant women interested in breastfeeding, maternity care practices that influence breastfeeding outcomes, breastfeeding preterm infants, breastfeeding's role in helping address disparities, and dispelling common myths. The tutorials contribute to achievement of 8 Healthy People 2020 Maternal, Infant and Child Health objectives.